2019
DOI: 10.1021/acsinfecdis.9b00224
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Phenotypical Characterization of Schistosoma mansoni Histone Deacetylase 8 (SmHDAC8) Inhibitors as Multistage Antischistosomal Agents

Abstract: Schistosomiasis (also known as bilharzia) is a neglected tropical disease caused by platyhelminths of the genus Schistosoma. The disease is endemic in tropical and subtropical areas of the world where water is infested by the intermediate parasite host, the snail. More than 800 million people live in endemic areas and more than 200 million are infected and require treatment. Praziquantel (PZQ) is the drug of choice for schistosomiasis treatment and transmission control being safe and very effective against adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…These differences should allow the development of inhibitors that are selective for the schistosome enzyme, thereby minimizing off‐target effects caused by interactions with the human (host) orthologues . A few smHDAC8 inhibitors have been described in the literature so far, such as J1038 and TH65 (Figure ) . These inhibitors are often aromatic hydroxamic acids and many exploit a hydrogen bond to the aforementioned histidine in the active site, whereas the methionine, which the human orthologue has in the same place, cannot be addressed in a similar fashion.…”
Section: Introductionmentioning
confidence: 99%
“…These differences should allow the development of inhibitors that are selective for the schistosome enzyme, thereby minimizing off‐target effects caused by interactions with the human (host) orthologues . A few smHDAC8 inhibitors have been described in the literature so far, such as J1038 and TH65 (Figure ) . These inhibitors are often aromatic hydroxamic acids and many exploit a hydrogen bond to the aforementioned histidine in the active site, whereas the methionine, which the human orthologue has in the same place, cannot be addressed in a similar fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Taking these concerns into consideration and given the modern resources of drug development, synthesis of PZQ derivatives [8], discovery of alternative lead compounds [9,10], natural products [11,12] and repurposing of existing drugs [13,14] are effective approaches for the introduction of new antischistosomal agents. Recently, we demonstrated that miltefosine (MFS), a membrane active alkylphosphocholine, is a promising repurposing candidate against schistosomiasis [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have shown some selective activity on SmHDAC8 over the major H. sapiens HDAC isoforms (HDAC1 and HDAC6), although the activities against SmHDAC8 and the human HDAC8 were similar [30]. HDACs inhibitors showing a preference for one isoform have been proposed as therapeutic compounds in cancer and other diseases, including parasitic diseases [30,[43][44][45][46]. This is because isoform-selective inhibitors can alter distinct pathways more specifically involved in disease mechanisms, contrary to broad-spectrum HDAC inhibitors, which can alter multiple cellular processes, thus causing higher toxic effects [43].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%